Causal Model of Extramarital Affairs Based on Attachment Styles and Early Maladaptive Schemas: Mediating Role of Marital Intimacy and Love Styles - Ensieh Bakhtiari; Saeedeh Hosseini; Mokhtar Arefi; Karim Afsharinia (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: Extramarital Affairs, as a traumatic event, can endanger a couple's marital life .This research has been designed and conducted in order to provide a predictive Causal model of the attitude of couples toward infidelity based on attachment styles and early maladaptive schemas, in addition to the mediating variable of marital intimacy, and love styles. Methods: Subjects include 650 married individuals (357 females and 293 males) living in Tehran in 2018 who were chosen using the convenience sampling method. Research data was gathered using Yung's early maladaptive schemas questionnaires, attachment styles, love styles, marital intimacy and attitude toward infidelity. Data analysis was done using the path analysis method and the AMOS statistical software. Results: Based on the direct effect of anxiety attachment, emotional deprivation, abandonment, social isolation, failure and vulnerability schemas on Eros love style, and the direct effect of anxiety attachment style and social isolation schema on Storge's love style, were significant (P≤0/05). Also, emotional deprivation, vulnerability, self-sacrifice, and Eros, Storge and Agape love-making styles had a direct effect on marital intimacy (P≤0/05) and the direct effect of anxiety attachment, Storge love style, enmeshment, vulnerability, self-sacrifice schemas, and intimacy on marital infidelity were significant (P≤0/05). Based on the values of comparative, absolute and relative indices, the tested model had a favorable fit. Conclusion: Since marriage and choosing a partner are among the most important decisions in life, the necessity of studying these predictive variables in premarital and family counseling to identify individuals exposed to risk must be emphasized upon.